Analisis Implementasi Kurikulum Merdeka Belajar dengan Scientific Approach pada Materi Perubahan dan Pelestarian Lingkungan Hidup di kelas X SMA Negeri 1 Batang Kuis: (Analysis of the Implementation of Independent Learning Curriculum with a Scientific Approach to the Material of Environmental Change and Conservation in Class X of SMA Negeri 1 Batang Kuis) - Sinurat, Rachel Saytama; Amrizal , Amrizal (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
The implementation of the independent learning curriculum using a scientific approach in biology learning has not been optimally implemented according to the planned implementation. This study aims to determine the implementation of the independent learning curriculum with a scientific approach on the material of environmental change and preservation in class X of SMA Negeri 1 Batang Kuis for the 2024/2025 academic year. The type of research used is descriptive quantitative with a survey method. The data collection technique for this study used teaching module analysis sheets, observation sheets, student questionnaires, and additional interviews. Data were analyzed using a percentage formula. The results showed that the lesson plans prepared by teachers were in accordance with the components of the independent curriculum by 81.25% (in the good category), and outlined the steps of scientific approach activities. Meanwhile, the implementation of the independent curriculum with a scientific approach in biology learning obtained a percentage of 82.14% in the good category, consisting of initial activities of 80.53% in the good category, core activities of 80.68% in the good category, and final activities of 85.21% in the good category. Meanwhile, the application of the Scientific Approach (5M) obtained 81.2% with a good category, the observing stage was 81.1%, asking was 64.3%, collecting data was 79.5%, associating was 90.2%, and communicating was 91.1%. The biology teacher of grade X has used an assessment based on the Independent Curriculum which consists of diagnostic, formative, and summative assessments. The conclusion of this study is that the implementation of the independent learning curriculum with a scientific approach on the material of environmental change and preservation in grade X of SMA Negeri 1 Batang Kuis for the 2024/2025 academic year at the planning stage is categorized as good, the overall implementation stage is categorized as good, and the assessment stage is categorized as good. Abstrak. Penelitian ini bertujuan untuk mengetahui implementasi kurikulum merdeka belajar dengan scientific approach pada materi perubahan dan pelestarian lingkungan hidup di kelas X SMA Negeri 1 Batang Kuis T.P 2024/2025. Desain penelitian yang digunakan yaitu deskriptif kuantitatif dengan metode survei. Teknik pengumpulan data penelitian ini dengan menggunakan lembar analisis modul ajar, lembar observasi, kuesioner peserta didik, dan tambahan berupa wawancara. Data dianalisis dengan menggunakan rumus persentase. Hasil penelitian menunjukkan bahwa perencanaan pembelajaran yang disusun guru memiliki kesesuaian dengan komponen kurikulum merdeka dengan kategori baik, dan menjabarkan langkah kegiatan scientific approach. Sementara implementasi kurikulum merdeka dengan scientific approach pada pembelajaran biologi dalam kategori baik, yang terdiri dari kegiatan awal dengan kategori baik, kegiatan inti dengan kategori baik, dan kegiatan akhir dengan kategori baik. Sedangkan penerapan Scientific Approach (5M) dalam kategori baik, meliputi tahapan mengamati dengan kategori baik, tahap menanya dalam kategori kurang, tahap mengumpulkan data dalam kategori cukup, tahap mengasosiasikan dalam kategori sangat baik, dan mengkomunikasikan dengan kategori sangat baik. Guru biologi kelas X telah menggunakan penilaian berdasarkan Kurikulum Merdeka yang terdiri dari asesmen diagnostik, formatif, dan sumatif dengan baik. Namun, guru jarang menggunakan rubrik penilaian sebagai pedoman dalam melakukan penilaian. Dapat disimpulkan bahwa implementasi kurikulum merdeka dengan Scientific Approach di kelas X SMA Negeri 1 Batang Kuis terlaksana dengan baik